Kur'an-ı kerimin makamsal tilaveti üzerine bir öğretim modeli önerisi - Savran, Tuğba (My University, 2021)
Güzel ses ve teğannî ile Kur'ân tilâvet etme ve bu tilâvetleri dinleme şeklinde gerçekleşen ibadetin, Hz. Peygamber dönemine kadar dayandığını, Müslümanlar nezdinde, oldukça önemli bir yere sahip olduğunu, söyleyebiliriz. Hz. Peygamber döneminde başlayan bu ritüelle ilgili rivayetlerde Hz. Peygamber; Kur'ân tilâvetinin, güzel sesle ve teğannî ile olması gerektiğini ifade etmiş, Kur'ân’ı, güzel ses ve teğannî ile tilâvet eden şahısları övmüş ayrıca Kur'ân’ı bir başkasından dinlemeyi sevdiğini ifade ederek, “Kur'ân dinleme” ibadetinin önemini göstermiştir. Kur'ân’ın makamsal (teğannî ve güzel ses ile) tilâveti, Kur'ân okumaya dair kuralların yanında, musiki ve ses eğitimine dair hususları da kullanmayı gerektiren, birkaç yetinin aynı anda ortaya konulmasının, lüzumlu olduğu icralardır. Dolayısıyla Kur'ân’ın makamsal tilâveti için disiplinler arası bir eğitim metodu izlenmelidir. Bu çerçevede geliştirilmiş sistemli bir çalışma metodu, talebenin eğitim süresini kısaltmasının yanında, icraların kalitesini ve talebelerin motivasyonunu da yükseltecektir. Bu çalışma, Kur'ân’ı makamsal tilâvet etmek isteyen talebelerle, Kur'ân’ın makamsal tilâveti hususunda eğitim veren icracılar için çerçeve bir metot oluşturma gayesi ile ortaya çıkmıştır. Çalışmada, Kur'ân tilâvetinde müzikal unsurların kullanımına dair tutum ve ihtiyaç, Kur'ân’ın tilâvetine, sadasına ve sanatlarına ait kavramlar, Kur'ân tilâvetinde temsîl ve temsîlin kaideleri ile Kur'ân tilâvetinde sesin kullanımı ve eğitimi konuları, ele alınmıştır.

We can say that worship, which takes place in the form of reciting the Qur'an with a beautiful voice and taghanni dates back to the times of Prophet Muhammad and has a very important place in the eyes of Muslims. In the narrations about this ritual which began during the Prophet's period, the Prophet stated that the recitations of the Quran should be in a beautiful voice and with taghanni, and he praised the individuals who recited the Quran with beautiful voice and taghanni, and he also expressed the importance of listening to the Quran worship, stating that he liked to listen to the Quran from someone else. Reciting the Quran with taghanni is a practice that requires the use of the Quran recitation rules along with the rules of related music and voice education, and it is necessary to put forward a few skills at the same time. Therefore, an interdisciplinary training method should be followed for the recitation of the Qur'an. In this context, a systematic study method will not only shorten the training period of the students, but will also increase the quality of the performances and the motivation of the students. This study aims to create a framework method for the students who want to recite the Qur'an and the performers who provide training on the recitation of the Qur'an. In the study, attitudes and needs regarding the use of musical elements in the Qur'an, concepts related to the verse, meaning and arts of the Qur'an, the principles of the Quran and the use and education of sound in the Qur'an are discussed. We can say that worship, which takes place in the form of reciting the Qur'an with a beautiful voice and taghanni dates back to the times of Prophet Muhammad and has a very important place in the eyes of Muslims. In the narrations about this ritual which began during the Prophet's period, the Prophet stated that the recitations of the Quran should be in a beautiful voice and with taghanni, and he praised the individuals who recited the Quran with beautiful voice and taghanni, and he also expressed the importance of listening to the Quran worship, stating that he liked to listen to the Quran from someone else. Reciting the Quran with taghanni is a practice that requires the use of the Quran recitation rules along with the rules of related music and voice education, and it is necessary to put forward a few skills at the same time. Therefore, an interdisciplinary training method should be followed for the recitation of the Qur'an. In this context, a systematic study method will not only shorten the training period of the students, but will also increase the quality of the performances and the motivation of the students. This study aims to create a framework method for the students who want to recite the Qur'an and the performers who provide training on the recitation of the Qur'an. In the study, attitudes and needs regarding the use of musical elements in the Qur'an, concepts related to the verse, meaning and arts of the Qur'an, the principles of the Quran and the use and education of sound in the Qur'an are discussed. We can say that worship, which takes place in the form of reciting the Qur'an with a beautiful voice and taghanni dates back to the times of Prophet Muhammad and has a very important place in the eyes of Muslims. In the narrations about this ritual which began during the Prophet's period, the Prophet stated that the recitations of the Quran should be in a beautiful voice and with taghanni, and he praised the individuals who recited the Quran with beautiful voice and taghanni, and he also expressed the importance of listening to the Quran worship, stating that he liked to listen to the Quran from someone else. Reciting the Quran with taghanni is a practice that requires the use of the Quran recitation rules along with the rules of related music and voice education, and it is necessary to put forward a few skills at the same time. Therefore, an interdisciplinary training method should be followed for the recitation of the Qur'an. In this context, a systematic study method will not only shorten the training period of the students, but will also increase the quality of the performances and the motivation of the students. This study aims to create a framework method for the students who want to recite the Qur'an and the performers who provide training on the recitation of the Qur'an. In the study, attitudes and needs regarding the use of musical elements in the Qur'an, concepts related to the verse, meaning and arts of the Qur'an, the principles of the Quran and the use and education of sound in the Qur'an are discussed.
Keywords: ashr-i sharif; aşr-ı şerif; fasıla; History; Islam; İslam; Kur'ân tilâveti; music; musiki; Recite the Our’an; spiritual reading; taghanni; Tarih; teğannî; temsîlî okuma